Author Correction: Modification of the head proteome of nurse honeybees (Apis mellifera) exposed to field-relevant doses of pesticides (Scientific Reports, (2020), 10, 1, (2190), 10.1038/s41598-020-59070-8) - Zaluski, Rodrigo (2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.